2012
DOI: 10.1158/0008-5472.can-11-3687
|View full text |Cite
|
Sign up to set email alerts
|

T-Regulatory Cells: Key Players in Tumor Immune Escape and Angiogenesis

Abstract: Regulatory T cells (Tregs) are found infiltrating tumors in a vast array of tumor types, and tumor-infiltrating Tregs are often associated with a poor clinical outcome. Tregs are potent immunosuppressive cells of the immune system that promote progression of cancer through their ability to limit antitumor immunity and promote angiogenesis. Here, we discuss the ways in which Tregs suppress the antitumor immune response, and elaborate on our recent discovery that Tregs make significant direct contributions to tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
585
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(600 citation statements)
references
References 107 publications
8
585
2
5
Order By: Relevance
“…In the tumor microenvironment, tumor-infiltrating immunosuppressive cells, including Treg cells, MDSCs, alternatively activated macrophages (M2), and immature/tolerogenic DC, inhibit anticancer immunity and play a role in tumor angiogenesis and cancer cell survival, proliferation, and metastatic potential. 50,51 In the present study, we delineated a role for NPC T-MDSCs in directly promoting NPC cell migration, invasion and metastasis. First, we found that T-MDSCs increase cancer migration and invasion via the induction of EMT in NPC cells in vitro.…”
Section: Discussionmentioning
confidence: 92%
“…In the tumor microenvironment, tumor-infiltrating immunosuppressive cells, including Treg cells, MDSCs, alternatively activated macrophages (M2), and immature/tolerogenic DC, inhibit anticancer immunity and play a role in tumor angiogenesis and cancer cell survival, proliferation, and metastatic potential. 50,51 In the present study, we delineated a role for NPC T-MDSCs in directly promoting NPC cell migration, invasion and metastasis. First, we found that T-MDSCs increase cancer migration and invasion via the induction of EMT in NPC cells in vitro.…”
Section: Discussionmentioning
confidence: 92%
“…The finding that this proliferation is much greater in mice with impaired Treg function suggests that the proliferation behaves similar to an immune system-sensitive carcinoma. The finding that depletion of Tregs allows progressive epithelial growth raises questions about the recent depletion of Tregs to enhance the immune response in cancer therapy (14).…”
Section: Epithelial Proliferationmentioning
confidence: 99%
“…This immune environment works to either suppress or promote cancer cell growth through various mechanisms. [7][8][9][10] For example, TILs are often observed in many types of solid tumors; in some cases they are considered to reflect the host immune system that responds to and eliminates the tumor cells. In fact, higher TIL infiltration has been reported to correlate with better prognosis in many tumor types, [11][12][13][14][15] including ovarian cancer for which a high degree of intratumoral CD8 C T cell was correlated with better clinical response to platinum agents.…”
Section: Introductionmentioning
confidence: 99%